Aging and binding in short-term memory: processes involved in conjunctive and relational binding. Issue 2 (7th February 2021) - Bastin, Christine; Besson, Gabriel
ABSTRACT: In visual short-term binding memory tasks, some studies suggested that aging disrupts relational binding more than conjunctive binding, whereas others report equivalent age-related differences in both types of binding. Yet, demands in controlled resources are potentially the greatest for relational short-term binding. In order to test the hypothesis that aging would affect preferentially tasks demanding in controlled processes, we assessed the contribution of controlled and automatic memory processes to relational and conjunctive short-term binding. Groups of young and older adults studied shape–colour (Exp.1 and 3) or object–colour (Exp.2) pairs in a relational condition in which items were linked to colour patches and a conjunctive condition where colour was integrated into the items. Memory for bindings was tested with a reconstruction task (Exp. 1 and 2) or with a recognition memory task (Exp. 3) under inclusion and exclusion instructions (Process Dissociation Procedure). The three experiments showed that the retrieval of both relational and conjunctive bindings relied primarily on controlled memory processes, the use of which was diminished in older participants. This study brings additional evidence that age-related differences in top-down control processes explain at least partly decreased short-term binding capacities.